What happens when a new government enters office? A comparison of ideological change in British and Swedish foreign policy 1991–2011. (March 2013) - Brommesson, Douglas; Ekengren, Ann-Marie
This study analyses to what extent a change of government in times of unchanged international structure affects the ideology of foreign policy. The main contribution is to investigate the role of political culture, as reflected through institutional design, as an intervening variable. Effects of changes of government in the United Kingdom in 1997 and 2010 and in Sweden in 1994 and 2006 is studied by analysing speeches in the General Debates of the UN General Assembly. The analysis is based on four ideal types. The results indicate that institutional design is an influencing intervening variable of foreign policy ideology. In the UK, a country dominated by majoritarian institutional design, foreign policy ideology changes more extensively in times of government change than in Sweden, a country dominated by consensual institutional design.